Effect of green juice and their bioactive compounds on genotoxicity induced by alkylating agents in mice. Issue 13 (3rd August 2017) - Fagundes, Gabriela Elibio; Damiani, Adriani Paganini; Borges, Gabriela Daminelli; Teixeira, Karina Oliveira; Jesus, Maiellen Martins; Daumann, Francine; Ramlov, Fernanda; Carvalho, Tiago; Leffa, Daniela Dimer; Rohr, Paula; Moraes De Andrade, Vanessa
ABSTRACT: Kale juice ( Brassica oleracea L. var. acephala D.C.) is a reliable source of dietary carotenoids and typically contains the highest concentrations of lutein (LT) and beta-carotene (BC) among green leafy vegetables. As a result of their antioxidant properties, dietary carotenoids are postulated to decrease the risk of disease occurrence, particularly certain cancers. The present study aimed to (1) examine the genotoxic and antigenotoxic activity of natural and commercially available juices derived from Brassica oleracea and (2) assess influence of LT or BC against DNA damage induced by alkylating agents such as methyl methanesulfonate (MS) or cyclophosphamide (CP) in vivo in mice. Male Swiss mice were divided into groups of 6 animals, which were treated with water, natural, or commercial Brassica oleraceae juices (kale), LT, BC, MMS, or CP. After treatment, DNA damage was determined in peripheral blood lymphocytes using the comet assay. Results demonstrated that none of the Brassica oleraceae juices or carotenoids produced genotoxic effects. In all examined cell types, kale juices or carotenoids inhibited DNA damage induced by MMS or CP administered either pre- or posttreatment by 50 and 20%, respectively. Under our experimental conditions, kale leaf juices alone exerted no marked genotoxic or clastogenic effects. However, a significant decrease in DNA damage induced by MMS or CP was noted. This effect was most pronounced in groups that received juices, rather than carotenoids, suggesting that the synergy among constituents present in the food matrix may be more beneficial than the action of single compounds. Data suggest that the antigenotoxic properties of kale juices may be of therapeutic importance.